High flow nasal cannula oxygen therapy in acute respiratory failure from acute exacerbation of fibrotic interstitial lung disease - Balzan, Fernanda Machado; Pacheco, Eder Chaves; Vieira, Fernando Nataniel; moretti Jr, Joares Luiz; Catarino, Bruna Maciel; Savi, Augusto (Clinical and Biomedical Research, 2020)
<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"><span id="docs-internal-guid-84b5c225-7fff-48e3-5297-df1d64bf1ed8" style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Introduction. High flow nasal cannula oxygen therapy (HFNC) has become frequent in the treatment of patients with acute hypoxemic respiratory failure. Methods. Eleven patients with acute exacerbation of fibrotic interstitial lung disease (ILD) were treated with HFNC after failure of conventional therapy (SatO<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">2<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">< 90% offering 100% FiO<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">2<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> by non-rebreathing mask or noninvasive ventilation). Results. Ten patients had success with HFNC (not requiring orotracheal intubation) during emergency department admission. HFNC significantly improves clinical variables after 2h: respiratory rate decreased from 33 ± 6 breaths/min to 23 ± 3 breaths/min; PaO<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">2<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> increased from 48.7 (38 - 59)mmHg to 81.1 (76 - 90) mmHg; PaO<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">2<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">/FiO<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">2<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> ratio increased from 102.4 ± 32.2 to 136.6 ± 29.4; SatO<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">2<span style="font-size: 12pt; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> increased from 85 (66 - 92)% to 96 ± (95 - 97)%. HFNC could be an effective alternative in the treatment of acute respiratory failure from acute exacerbations of fibrotic ILD.